Karakterisasi Abu Sekam Padi dengan Menggunakan XRD - samik samik; Nita Kusumawati; Maria Monica Sianita; Dina Kartika Maharani; Amalia Putri Purnamasari; Mukhlash Imaduddin; M Iqbal Al Ghifari (Unesa Journal of Chemistry, 2022)
Rice husk ash is a material that mostly contains silica (SiO2). Silica can be used as a raw material for various industries. This research is an experimental study, covering the synthesis of rice husk ash with various calcination temperatures, namely 800 oC, 900 oC, and 1000 oC. The purpose of this study was to identify the type of solid and crystalline phases of RHA so that the results of this study could be used as a basis for further research on the use of RHA. The results of the synthesis produced four types of samples, namely samples calcined at a temperature of 800 oC (coded S-800), calcined at 900 oC was gray (S-900 A), calcined at 900 oC was white (S-900 P), and samples were calcined at a temperature of 1000 oC (S-1000). Characterization using X-Ray Diffraction (XRD) showed that all samples included crystalline solids with the tridymite crystal phase and cristobalite were detected in samples S-800, S-900 P, S-900 A, and S-1000. Cristobalite and tridymite are silica mineral polymorphs with the same chemical formula as quartz, SiO2, but have different crystal structures. The percentage of crystallinity of the sample was calculated by comparing the sample which has the highest peak intensity (S-1000). The crystallinity results for S-1000, S-900 P, and S-900 A were 100%, 96%, 79%, and 32%. The lower the calcination temperature, the smaller the percentage of crystallinity. Keywords: rice husk ash, calcined, silica, XRD, crystalline solid